2021
DOI: 10.1096/fj.202002524r
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol‐enhanced SIRT1‐mediated osteogenesis in porous endplates attenuates low back pain and anxiety behaviors

Abstract: Low back pain (LBP) is a major clinical problem that lacks effective treatments. The sensory innervation in porous vertebral endplates and anxiety contributes to spinal hyperalgesia. We hypothesized that SIRT1 activator resveratrol alleviates LBP and anxiety via promotion of osteogenesis in the porous endplates. The hyperalgesia and anxiety‐related behaviors; sensory innervation, inflammation and porosity of endplates; and osteogenic/osteoclastic factors expression were measured following resveratrol treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Moreover, resveratrol could ameliorate anxiety-like behavior and social dysfunction induced by adolescent social isolation and increase NAc ATP levels as well as the number of mitochondria. Indeed, the anti-anxiety and antidepressant effects of resveratrol have been studied in a variety of animal models [ 28 ], and numerous studies demonstrated that resveratrol produces anxiolytic and antidepressant by regulating inflammation, oxidative stress, hypothalamic⁻pituitary⁻adrenal axis and neurogenesis [ 24 , 25 , 53 ]. For example, Sahin TD reported that resveratrol ameliorated streptozotocin-induced anxiety and depressive-like behaviors by inhibition of oxidative stress [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, resveratrol could ameliorate anxiety-like behavior and social dysfunction induced by adolescent social isolation and increase NAc ATP levels as well as the number of mitochondria. Indeed, the anti-anxiety and antidepressant effects of resveratrol have been studied in a variety of animal models [ 28 ], and numerous studies demonstrated that resveratrol produces anxiolytic and antidepressant by regulating inflammation, oxidative stress, hypothalamic⁻pituitary⁻adrenal axis and neurogenesis [ 24 , 25 , 53 ]. For example, Sahin TD reported that resveratrol ameliorated streptozotocin-induced anxiety and depressive-like behaviors by inhibition of oxidative stress [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that resveratrol could ameliorate social-defeat-stress-induced depressive-like behavior and locus coeruleus neuroinflammation [ 28 ]. A recent study also demonstrated that resveratrol alleviated anxiety-like behavior induced by lumbar spine instability surgery and relieved inflammation in the hippocampus [ 53 ]. Although a large number of studies have been carried out on the antidepressant mechanism of resveratrol [ 25 ], the therapeutic effect of resveratrol on adolescent depression and anxiety and the potential mechanism underlying resveratrol effects in the NAc remain largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of Sirt1 can modulate related signaling pathways, alleviating pathological pain (Jia et al, 2020;Li et al, 2019;Lv et al, 2021). Q.…”
Section: Silent Information Regulator 1 Signaling Pathwaymentioning
confidence: 99%
“…By inhibiting cyclooxygenase activity, Sirt1 reduces inflammation and safeguards against neurological injury. Overexpression of Sirt1 can modulate related signaling pathways, alleviating pathological pain (Jia et al, 2020; Li et al, 2019; Lv et al, 2021). Q. Yin et al (2013) demonstrated that intrathecal resveratrol injections diminished mechanical allodynia and thermal nociceptive sensitization in chronic constriction injury (CCI) rats while increasing Sirt1 expression.…”
Section: Resveratrol and Its Modulation Of Pathological Pain Via Dive...mentioning
confidence: 99%
“…Drugs which could suppress the activities of osteoclasts such denosumab have shown analgesic effects in patients with Modic changes related LBP 14 . Therefore, the inhibition of osteoclastogenesis might prevent the local pathologic change and decrease the sensory innervation in endplates, which could be a potential strategy for LBP treatment 16 .…”
Section: Introductionmentioning
confidence: 99%